2022
DOI: 10.48550/arxiv.2203.01796
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sleptonic SUSY: From UV Framework to IR Phenomenology

Kaustubh Agashe,
Majid Ekhterachian,
Zhen Liu
et al.

Abstract: We study an attractive scenario, "Sleptonic SUSY", which reconciles the 125 GeV Higgs scalar and the non-observation of superpartners thus far with potentially pivotal roles for slepton phenomenology: providing viable ongoing targets for LHC discovery, incorporating a co-annihilation partner for detectable thermal relic dark matter, and capable of mediating the existing muon g −2 anomaly. This is accomplished by a modestly hierarchical spectrum, with sub-TeV sleptons and electroweakinos and with multi-TeV mass… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 122 publications
(200 reference statements)
0
6
0
Order By: Relevance
“…Still, this provides valuable information to understand the situation with scalar doublets at the loop level. One can consider extending the considerations to multiple specifies, mainly through lepton partners, e.g., light staus [35,36]. These can be a promising direction to explore.…”
Section: Degenerate Top-squark Soft Massesmentioning
confidence: 99%
“…Still, this provides valuable information to understand the situation with scalar doublets at the loop level. One can consider extending the considerations to multiple specifies, mainly through lepton partners, e.g., light staus [35,36]. These can be a promising direction to explore.…”
Section: Degenerate Top-squark Soft Massesmentioning
confidence: 99%
“…This spectrum bears some resemblance to those studied from a UV perspective in ref. [8] in the context of the hierarchy problem and the muon (g − 2). The LHC bounds were compared to the flavor constraints for a similar spectrum in ref.…”
Section: Charged Lepton Flavor Violation In the Mssmmentioning
confidence: 99%
“…2 An important theoretical consideration, which we do not consider here, is can g µ −2 be explained in models consistent with grand unification. It was shown that, at least in some unification models, it can be rectified [14,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The CP-problem is solved by assuming a shift symmetry where the imaginary part of the SUSY breaking field receives a constant shift[35]. See also[28] for another construction of a CP-safe gaugino mediation model 5. In Ref [42],.…”
mentioning
confidence: 99%